Energy insecurity and community resilience: The experiences of Bedouins in Southern Israel. Issue 124 (October 2021) - Shapira, Stav; Shibli, Haneen; Teschner, Naama
Highlights: We report a significant association between energy insecurity and community resilience among Bedouins in southern Israel. We offer new insights into how energy insecurity is manifested in two settlement types: townships and off-grid villages. Energy insecurity is perceived both as a personal crisis, and as a communal problem, and depends largely on levels of trust. Reducing energy insecurity can support rural communities during routine as well as emergencies. Abstract: Energy insecurity has been recognized as a global social and public health challenge. Availability of and accessibility to energy infrastructure is a core element of community resilience—a concept that characterizes a community's ability to promote health and well-being, and to cope with and recover from adversity. We conducted a quantitative survey in order to explore the interplay between these two experiences among residents of two types of Bedouin communities in Southern Israel: townships and informal settlements, which differ in their accessibility to energy infrastructure. We report a significant negative association between experiences of energy insecurity and perceived community resilience, especially with regard to trust in leadership and emergency preparedness. This indicates that energy insecurity is not only a personal or a household burden, but rather an issue that has broader communal and social aspects (and consequences) –one that should be tackled at the local and municipal levels. Our study deepens the current understanding of the processes and factors that may promote or impede community resilience and health by establishing a clear link between place-related physical and perceptual resources.